A study on alterations in functional activity in migraineurs during the interictal period. Issue 1 (January 2023) - Wu, Lanxiang; Wang, Xuan; Liu, Qian; Chai, Lijun; Tian, Sheng; Wu, Wei
Abstract: Migraine is a recurrent disease in which the cumulative effect of repeated pain attacks over a long period of time causes changes in brain function. Although there are some studies focusing on the interictal period of migraine, the reproducibility of these results is poor. Therefore, we intend to use a data-driven functional connectivity (FC) approach to probe the alterations in cerebral functional activity during the interictal period, as well as underlying no-task mechanisms of inducing headache attack in migraine patients. In the current research, 24 episodic migraine patients and 23 healthy controls (HCs) were recruited. By analyzing the magnitude of regional homogeneity (ReHo) and low-frequency fractional fluctuation (fALFF), We identified alterations in spontaneous brain activity in migraineurs, including the bilateral middle frontal gyrus, left postcentral, and right lingual gyrus. Thereafter such abnormalities were selected as seeds (ROIs) for FC analysis to further explore the underlying changes between ROIs and the whole brain areas. Compared with HCs, FC between the right middle frontal gyrus with the left precuneus cortex, and bilateral thalamus were enhanced in migraineurs. In addition, increased FC has been showed between the left postcentral gyrus with the bilateral thalamus. Furthermore, negative correlation existed between fALFF values of the left middle frontal gyrus and the pain intensity of migraine attacks (r = −0.4578, p = 0.0245). In summary, abnormal FC between the bilateral thalamus and right middle frontal gyrus, or the left retrocentral gyrus may occur between attacks in migraineurs, which may be the basis for sensory integration and pain regulation dysfunction. Thus, this could become a promising biomarker for the early diagnosis and evaluation of migraine in the interictal period, and provide a novel view for further investigation of the pathogenesis and etiology of recurrent migraine. Highlights: Resting-state fMRI is an advanced tool for studying neurological disorders. fALFFs were increased in the left MFG, and werenegatively correlated with pain intensity of migraine attacks. ReHo in the right MFG was enhanced, while the value in the right LING, left POCG was decreased. migraineurs showed increased FC of the right MFG with bilateral THA, and the PCUN. migraineurs showed increased FC of the left POCG with bilateral THA. Abstract : Migraine; Interictal period; Resting-state fMRI; Functional connectivity.